HAMBATAN PENYELENGGARAAN LAYANAN BIMBINGAN KELOMPOK OLEH GURU BK DI SMA NEGERI KOTA PADANG - Nurlela, Nurlela; Said, Azrul; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
Based on phenomenon that researcher found, there are some counselors have some obstacle in guidance of group. the researchers raised concerns about the study: what are the obstacle in guidance of group by the counselors in SMA Negeri Padang City. The purpose of this study is to describe: 1) the obstacle of counselors in doing guidance of group connected by medium and infrastructure. 2) the obstacle of counselors Â in doing guidance of group connected by the time. 3) the obstacle of guidance adn counseling teachers connected by the stage of organize guidance of group. This research is a descriptive. The population of this research is all the counselors in SMA Negeri Padang City, amounting 89 teachers. The technique that used for took the sample was multistage random sampling. The sample of this research was 17 teachers. The instrument was questinnaire. And technique of data analysis was persentage. The result of this research showed that: 1) obstacle counselors connected by medium and infrastucture categorized at much. 2) obstacle counselors connected by time categorized too much. 3) obstacle counselors Â connected by organize guidance of group categorizedÂ too much.